1989
DOI: 10.1037/h0084209
|View full text |Cite
|
Sign up to set email alerts
|

Training new, nonnative speech contrasts: A comparison of the prototype and perceptual fading techniques.

Abstract: We trained unilingual adull Canadian francophone listeners to identify the English voiceless and voiced linguadcntal ("th") frictives, 101 and /&/, using synthetic exemplars of each phoneme. Identification training with feedback improved listeners' abilities to identify both natural and synthetic tokens. These results show that training with appropriately selected prototype stimuli can produce a linguistically meaningful improvement in a listener's ability to identify new, nonnative speech sounds -both natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 15 publications
2
46
0
Order By: Relevance
“…Both successful as well as unsuccessful training and generalization attempts subsequently have led to the conclusion that the adult system does not lose the ability to acquire new linguistic contrasts, provided specific experimental procedures are used to train the listeners ͑Carney et Aslin and Pisoni, 1980;Strange and Dittmann, 1984;Jamieson and Morosan, 1989;Pisoni et al, 1982;Werker and Tees, 1984a;Lively et al, 1993Lively et al, , 1994Logan et al, 1991͒. Until now, this line of research has been limited to behavioral studies.…”
Section: Plasticity Of the Adult Systemmentioning
confidence: 99%
“…Both successful as well as unsuccessful training and generalization attempts subsequently have led to the conclusion that the adult system does not lose the ability to acquire new linguistic contrasts, provided specific experimental procedures are used to train the listeners ͑Carney et Aslin and Pisoni, 1980;Strange and Dittmann, 1984;Jamieson and Morosan, 1989;Pisoni et al, 1982;Werker and Tees, 1984a;Lively et al, 1993Lively et al, , 1994Logan et al, 1991͒. Until now, this line of research has been limited to behavioral studies.…”
Section: Plasticity Of the Adult Systemmentioning
confidence: 99%
“…As a result, the trainees were able to learn to discriminate the training stimuli but were not able to transfer this learning to new stimuli and contexts. In more recent attempts at L2 training, it has become clear that added variance in the training set ͑e.g., more speakers, more phonetic contexts͒ aids learning and generalization ͑Bradlow et al Jamieson and Morosan, 1989;Lively et al, 1993͒. It is quite possible that a major benefit of high-variability training is that less informative cues will vary more within a category across multiple exemplars while more informative cues will be relatively more stable.…”
Section: A Implications For L2 Phonetic Acquisitionmentioning
confidence: 99%
“…For example, Lively, Logan, and Pisoni (Lively et al, 1993) found that Japanese listeners trained to identify /r/ and /l/ in one talker's voice did not improve in identifying /r/ and /l/ produced by an unfamiliar talker, whereas listeners trained on multiple talkers did. Such studies have established that careful selection of varied phonetic tokens facilitates the generalization of perceptual training over a closed stimulus set in adults (Bradlow et al, 1996;Jamieson and Morosan, 1989;Logan et al, 1991). Pisoni (1992) suggests that variation provides insight into invariant features.…”
Section: Introductionmentioning
confidence: 99%